2022
DOI: 10.1128/spectrum.01082-22
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Streptococcus agalactiae Colonizing Nonpregnant Adults Support the Opportunistic Nature of Invasive Infections

Abstract: The increasing incidence of Streptococcus agalactiae (group B streptococci [GBS]) infections in adults and the inability of antimicrobial prophylaxis peripartum to control late-onset infections in infants motivate the study of the asymptomatic carrier state in nonpregnant adults. We found an overall carriage rate like that of pregnant women, increasing with age, potentially contributing to the higher incidence of GBS infections with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We found that the abundance of GBS varied by orders of magnitude between individuals with GBS and there was no difference in the carrier frequency or abundance based on gender. These data indicate that GBS is common in the distal GI tracts of the general population, providing further evidence that the distal GI tract is an important reservoir for GBS in the human body [17,28].…”
Section: Subgroup Analysis Of Associations Of Gbs For Self-identified...supporting
confidence: 52%
See 3 more Smart Citations
“…We found that the abundance of GBS varied by orders of magnitude between individuals with GBS and there was no difference in the carrier frequency or abundance based on gender. These data indicate that GBS is common in the distal GI tracts of the general population, providing further evidence that the distal GI tract is an important reservoir for GBS in the human body [17,28].…”
Section: Subgroup Analysis Of Associations Of Gbs For Self-identified...supporting
confidence: 52%
“…in GBS colonization, considering previous observations of high prevalence of oral GBS colonization [28].…”
Section: Availability Of Data and Materialsmentioning
confidence: 71%
See 2 more Smart Citations
“…We should be attention to each detail of detection procedure and to ensure detection accuracy.This study was conducted to be ignored problem and to make up for the lack of data in this eld.The results shown that it is higher positive detection rate of streptococcus agalactiae with enrichment comapared with without enrichment method. As mentioned in CDC revised consensus guidelines were as many as 50% of streptococcus agalactiae carriers culture results are false negative in without enrichment [35]. Our results shown that the streptococcus agalactiae colonization rate of pregnant women were 8.41%~8.90% with enrichment culture.…”
Section: Discussionmentioning
confidence: 49%